1995
DOI: 10.1029/94jc02721
|View full text |Cite
|
Sign up to set email alerts
|

A tidal model for eastern Juan de Fuca Strait and the southern Strait of Georgia

Abstract: A three-dimensional, barotropic, finite element model is used to calculate the tidal flows in eastern Juan de Fuca Strait and the southern Strait of Georgia. The harmonics of eight constituents are computed and compared with those from previous finite difference models and those from historical tide gauge and current meter observations. Root-mean-square differences between observed and calculated sea level amplitudes are within 2.0 cm for all constituents, and the phases are within 4.0 ø for all constituents e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(81 citation statements)
references
References 30 publications
4
76
0
1
Order By: Relevance
“…The analysis of a 38 year long time series at Victoria (southern edge of Vancouver Island) demonstrated that the amplitude of harmonic M 2 at this site varies by approximately 6.5% (37.3 ± 2.4 cm). The maximum amplitudes of M 2 are consistently observed in JulyAugust, while the minimum amplitudes are in Febru ary-March [15]. M. Foreman introduced artificial har monics H 1 and H 2 to take into account the seasonal variability of M 2 and to increase the accuracy of tidal forecasting (such harmonics in the decomposition of the tidal potential are absent [9]) 1 , whose frequencies are related to the M 2 frequency as…”
Section: Discussionmentioning
confidence: 95%
“…The analysis of a 38 year long time series at Victoria (southern edge of Vancouver Island) demonstrated that the amplitude of harmonic M 2 at this site varies by approximately 6.5% (37.3 ± 2.4 cm). The maximum amplitudes of M 2 are consistently observed in JulyAugust, while the minimum amplitudes are in Febru ary-March [15]. M. Foreman introduced artificial har monics H 1 and H 2 to take into account the seasonal variability of M 2 and to increase the accuracy of tidal forecasting (such harmonics in the decomposition of the tidal potential are absent [9]) 1 , whose frequencies are related to the M 2 frequency as…”
Section: Discussionmentioning
confidence: 95%
“…The solid diamonds represent data, the line a linear regression on the data (r 2 = 0.6; n = 15). Tidal currents were computed with a three-dimensional, barotropic, finite element tidal model, including eight tidal constituents (Foreman et al, 1995).…”
Section: Effect Of Phytoplankton Blooms On Transmissivitymentioning
confidence: 99%
“…Some recent applications to tidal problems are given in e.g. Foreman et al (1993Foreman et al ( , 1995, Fortunato et al (1997), Ip et al (1998), Legrand et al (2006Legrand et al ( , 2007, Levasseur (2007), Lynch et al (1993Lynch et al ( , 2004 and Walters (1992). A comparison of the performance of finite difference and finite element models for reproducing the M 2 tide and its higher harmonics in the English Channel was performed by Werner (1995).…”
Section: Introductionmentioning
confidence: 99%